KOMUNIKASI NON VERBAL GURU PADA MURID TUNARUNGU SEKOLAH DASAR LUAR BIASA NEGERI DESA KELEYAN KECAMATAN SOCAH KABUPATEN BANGKALAN - Alfan Roziqi; Dinara Maya Julijanti (Jurusan Ilmu Komunikasi UTM, 2015)
The process of communication can occur in anytime and anywhere. One of them is communication during the learning process at school. Communication that happen during the learning process usually applies verbal as the media (written form and reading utterence), while at school for the disabilities – the deaf for example- the communication applied is non verbal. Therefore, the purpose of the study is to determine the non verbal communication between deaf students and their teachers at Keleyan Stated Elementary School for the Disabilities.